Kajian ekonomi usaha pembesaran Ikan Bandeng (Chanos chanos forskal) di kolam beton air payau FPIK UHO - Yulipriani; Nurdiana A; Piliana, Wa Ode; Balubi, Abdul Muis; Siang, Roslindah Daeng; Hamzah, Muhaimin (Universitas Halu Oleo, 2023)
The purpose of this study was to find out the total cost, production of milk fish, total revenue, the profit, RC Ratio BEP Price, BEP Revenue and BEP production of milkfish culture business. This research was conducted on July 2022 at brackish water concrete pond in Faculty of Fisheries and Marine Sciences, Halu Oleo University (as a case study). The results showed that the fixed costs was IDR127,583 and the variable costs was IDR5,005,000, so the total cost was IDR5,132,583/production. The total revenue of this business was IDR 17,500,000 and the production Break Event Point (kg) was 6.00. the total price of Break Event Point was IDR6,415.73 and the total revenue of Break Even Point was IDR447,660. The profit of milkfish culture business in this location was IDR12,367,417 and the RC ratio of this business was 3.41. The milkfish culture business has a significant influence on the some indicators of economically benefit. This study concluded that the milkfish culture business at brackish water of Faculty of Fisheries and Marine Science, Halu Oleo University could profits because the total revenue could cover the production costs of milkfish culture business.